Design with denim. A process that impacts health and ethics - Vilchis Esquivel, Luz del Carmen (Seven Editora, 2023)
This is a reflection on the ethical and moral implications of the Sandblast Case, named for the technique used to wear down jeans; the issue also includes the trafficking of children to harvest cotton used in the manufacture of denim (each pair of pants can be between 75% and 100% cotton). The media scandal has arisen due to the delicate repercussions on the health and lives of both workers in the fashion industry and consumers of the garments, resulting from this production process. Along with the above, there is the indifference and voracity of transnational brands that have no qualms about continuing these practices by hiring workers in a state of defenselessness, as in the case of children, or risking the lives of many. DOI:https://doi.org/10.56238/sevened2023.004-035